1994
DOI: 10.1111/j.1151-2916.1994.tb07047.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of a Particulate‐Diamond‐Reinforced Cordierite Matrix Composite

Abstract: The effect of 15 vol% particulate diamond reinforcement on the thermal conductivity of a cordierite matrix was studied as a function of diamond particle size from room temperature to 700°C. The thermal conductivity was found to increase with increasing particle size to a maximum increase of about 75% for a mean particle size of 50 pm. The particle size effect was found to be more pronounced at the lower temperatures than at the higher temperatures. The observed effect of particle size and temperature was attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…In the YSZ/Al 2 O 3 composite system, the difference between the Young's moduli of YSZ and Al 2 O 3 (E Al 2 O 3 /ρ Al 2 O 3 · ρ YSZ /E YSZ < 3) is not large enough to have an obvious influence on the phonon transmission probability. Hasselman et al 26 found the interfacial thermal barrier in a cordierite-diamond composite is less than 1.0 × 10 −8 m 2 K/W at 400 • C, while the Young's modulus of diamond is almost ten times higher than that of cordierite (the density of diamond and cordierite is 3.51 and 2.52 g/cm 3 , respectively). Therefore, it is possible that the thermal resistance of the YSZ/Al 2 O 3 interface is even smaller than that value.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the YSZ/Al 2 O 3 composite system, the difference between the Young's moduli of YSZ and Al 2 O 3 (E Al 2 O 3 /ρ Al 2 O 3 · ρ YSZ /E YSZ < 3) is not large enough to have an obvious influence on the phonon transmission probability. Hasselman et al 26 found the interfacial thermal barrier in a cordierite-diamond composite is less than 1.0 × 10 −8 m 2 K/W at 400 • C, while the Young's modulus of diamond is almost ten times higher than that of cordierite (the density of diamond and cordierite is 3.51 and 2.52 g/cm 3 , respectively). Therefore, it is possible that the thermal resistance of the YSZ/Al 2 O 3 interface is even smaller than that value.…”
Section: Resultsmentioning
confidence: 97%
“…25 Another origin of the Kapitza resistance is the elastic discontinuity at the heterogeneous interface. 26 It is well known that the thermal conductivity of a material is expressed as…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, at lower content of SiC, interfacial thermal resistance tends to decrease the thermal conductivity of composites, while at higher content of SiC, the enhancement due to percolative heat conduction paths of the dispersions counteracts the decreasing effect of interfacial thermal resistance on the composite thermal conductivity. And hence, the thermal conductivity of composites decreases and then increases with increasing volume fraction of SiC, which is interesting and not mentioned in previous works [1][2][3][4][5][6]8) …”
Section: Effect Of Interfacial Thermal Resistance Andmentioning
confidence: 89%
“…Effective thermal conductivity of composite materials is usually determined not only by the constituent conductivities, volume fraction, shape and microscale arrangement but also by interfacial thermal resistance between the constituent phases. [1][2][3][4][5][6] The interfacial thermal resistance (the reciprocal of interfacial thermal conductance) is possibly attributable to two factors: 7) (a) thermal contact resistance due to poor mechanical and chemical bonding between constituent phases and (b) thermal boundary resistance due to differences in the physical properties of the composite's constituents, also known as Kapitza resistance due to the diffuse scattering of phonons at interfaces. 8) The interfacial thermal resistance in a composite refers to the combined effect of the thermal contact resistance and the thermal boundary resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Material properties at room temperature used in the calculations[18,[29][30][31][32][33][34]. The value of the interfacial thermal resistance (ITR) between the metal and the resin.…”
mentioning
confidence: 99%